Effect of light and temperature on germination of Costus arabicus L., seeds an tropical ornamental species - Santos, Nara Oshiro; Tavares, Armando Reis; Kanashiro, Shoey; Santos, Vanessa Rebouças do (Ornamental Horticulture, 2016)
Costus arabicus L. (Costaceae) is a tropical species native from Brazil. The species has ornamental potential as garden and vase plant, and for flower and stem cutting. The aim of this study was to evaluate the seed germination of C. arabicus under different of light and temperature conditions. Seeds subjected to constant temperatures of 20, 25 and 30 °C under photoperiod of 12 h of light or dark. The parameters analyzed were percentage of germination and germination speed index (GSI). The highest germination percentage (70%) was under temperature of 30 °C, both in light or dark. The GSI showed that the germination rate increases as temperature increases, mainly on 30 °C. C. arabicus seeds germinated in the presence or absence of light, thus was considered neutral photoblastic and germination on light under 30 °C was more efficient for seed germination.